Efficient gene editing in Corynebacterium glutamicum using the CRISPR/Cas9 system - Feng Peng (Microbial Cell Factories, 2017)
Abstract Background Corynebacterium glutamicum (C. glutamicum) has traditionally been used as a microbial cell factory for the industrial production of many amino acids and other industrially important commodities. C. glutamicum has recently been established as a host for recombinant protein expression; however, some intrinsic disadvantages could be improved by genetic modification. Gene editing techniques, such as deletion, insertion, or replacement, are important tools for modifying chromosomes. Results In this research, we report a CRISPR/Cas9 system in C. glutamicum for rapid and efficient genome editing, including gene deletion and insertion. The system consists of two plasmids: one containing a target-specific guide RNA and a homologous sequence to a target gene, the other expressing Cas9 protein. With high efficiency (up to 100%), this system was used to disrupt the porB, mepA, clpX and Ncgl0911 genes, which affect the ability to express proteins. The porB- and mepA-deletion strains had enhanced expression of green fluorescent protein, compared with the wild-type stain. This system can also be used to engineer point mutations and gene insertions. Conclusions In this study, we adapted the CRISPR/Cas9 system from S. pyogens to gene deletion, point mutations and insertion in C. glutamicum. Compared with published genome modification methods, methods based on the CRISPR/Cas9 system can rapidly and efficiently achieve genome editing. Our research provides a powerful tool for facilitating the study of gene function, metabolic pathways, and enhanced productivity in C. glutamicum.